Drivers and barriers toward reducing meat consumption - Cheah, Isaac; Shimul, Anwar Sadat; Liang, Johan; Phau, Ian (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2020)
The purpose of this paper is to explore the consumers' attitude and intention toward reducing meat consumption. In exploring such, the influence of social norm, perceived benefits, perceived barrier and environmental concern are examined. A self-administered online survey was employed for data collection. A sample of 298 Australians was analysed through structural equation modelling with SPSS AMOS 25. Social norm, perceived benefits and barriers as well as environmental concerns had significant impact on the consumers’ attitude toward reducing meat consumption. The findings of this paper validate and extend the theoretical framework on dietary behaviour change in particular one that involves reducing the consumption of meat. The findings provide valuable insights to food producers and the food industry, as well as health professionals as it highlights the linkages between meat consumption reduction and a broad array of motivations such as health and care for the environment. The study provides insights into the motivations of individuals to limit their meat consumption. More importantly, it also systematically examines the perceived benefits and barriers of meat consumption thus shedding insights on the opportunities for dietary behaviour change and public health.